2018
DOI: 10.1111/brv.12472
|View full text |Cite
|
Sign up to set email alerts
|

The community and ecosystem consequences of intraspecific diversity: a meta‐analysis

Abstract: Understanding the relationships between biodiversity and ecosystem functioning has major implications. Biodiversity–ecosystem functioning relationships are generally investigated at the interspecific level, although intraspecific diversity (i.e. within‐species diversity) is increasingly perceived as an important ecological facet of biodiversity. Here, we provide a quantitative and integrative synthesis testing, across diverse plant and animal species, whether intraspecific diversity is a major driver of commun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
189
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 240 publications
(203 citation statements)
references
References 154 publications
12
189
1
1
Order By: Relevance
“…Importantly, this approach has demonstrated that ecologically driven adaptive phenotypic changes can feed back directly to ecology [e.g. population growth and ecosystem function (Thuiller et al ., ; Raffard et al ., )] – illustrating the reciprocity between ecological and evolutionary processes (Metz, Nisbet, & Geritz, ; Post & Palkovacs, ; Kinnison, Hairston, & Hendry, ). Studies of eco‐evo dynamics recognize that substantial evolutionary changes can occur at ecological time scales (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this approach has demonstrated that ecologically driven adaptive phenotypic changes can feed back directly to ecology [e.g. population growth and ecosystem function (Thuiller et al ., ; Raffard et al ., )] – illustrating the reciprocity between ecological and evolutionary processes (Metz, Nisbet, & Geritz, ; Post & Palkovacs, ; Kinnison, Hairston, & Hendry, ). Studies of eco‐evo dynamics recognize that substantial evolutionary changes can occur at ecological time scales (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Intraspecific variation has been shown to be comparable to, and in some cases even more important than, interspecific variation (Des Roches et al., ). In plant populations, intraspecific variation can have far‐reaching effects, from structuring associated arthropod, endophyte and secondary consumer communities (Kagiya, Yasugi, Kudoh, Nagano, & Utsumi, ; Koricheva & Hayes, ; Lamit et al., , ; Raffard, Santoul, Cucherousset, & Blanchet, ) to governing ecosystem processes, such as nutrient cycling and primary production (Crutsinger et al., ; Hughes, Inouye, Johnson, Underwood, & Vellend, ; Madritch, Greene, & Lindroth, ). These effects can have fitness consequences for interacting organisms, leading to changes in evolutionary trajectories and contributing to eco‐evolutionary dynamics (Raffard, Santoul, et al., ; Whitham et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Intraspecific variability is now widely recognized as playing a crucial role in evolutionary and ecological processes (Read, Hoban, Eppinga, Schweitzer, & Bailey, 2016;Violle et al, 2012). Genetic and/or phenotypic differences among conspecific individuals can have important implications for community structure and ecosystem functioning by mediating the intensity of bottom-up or top-down processes (see review in Des Roches et al, 2017;Raffard, Santoul, Cucherousset, & Blanchet, 2018). Biological invasions provide a unique opportunity to study intraspecific variability in recently established populations.…”
Section: Introductionmentioning
confidence: 99%